Ferroelectric switching and dielectric response of P(VDF-TrFE)/PMMA blends - Moreira, Roberte L.; Faria, Luiz O.; Wisniewski, Célio; Giacometti, José A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
The ferroelectric and the dielectric behaviors of binary blends formed by an equi-molar Poly(vinylidene fluoride trifluoroethylene) copolymer [P(VDF-TrFE)] and Poly(methyl methacrylate) [PMMA] were investigated, for several PMMA compositions. For 40 wt.% or more PMMA contents, the blends are completely amorphous. Below this value, they crystallize in the usual Cm2m polar structure of P(VDF-TrFE). The ferroelectric switching characteristics and the dielectric response of the blends demonstrate the formation of dynamically stable ferroelectric domains. Moreover, the blended films are highly transparent in the optical region. Therefore, thin films of these binary blends are good candidates as host materials for nonlinear optical applications.
Keywords: Amorphous materials; Crystallization; Ferroelectric materials; Nonlinear optics; Polymethyl methacrylates; Binary blends; Dielectric response; Ferroelectric domains; Ferroelectric switching; Polymer blends